2015
DOI: 10.1007/s11223-015-9632-4
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Static and Dynamic Characteristics of the EDM Machine Based on the ANSYS Workbench

Abstract: The static and dynamic characteristics of the EDM machine as the main machining unit directly influence the machining accuracy and stability. For a particular type of the EDM machine, the three-dimensional model was built with SolidWorks and the finite element method was employed with the ANSYS Workbench to analyze the static and dynamic characteristics of the machine. The results show that the stiffness of the ram and vertical guide (Z-axis) in the Y and Z directions is the weak side of the machine. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The rapid development of computational techniques based on the finite element method (FEM) allows vibration analysis of the systems of complex geometry and design to be conducted [1]. In [2], the finite element (FE) models are used to analyze the static and dynamic behavior of the EDM (electrical discharge machining) machine. The authors [3] analyzed cyclically loaded gear vibrations with a power circulation test rig configuration using FEM techniques.…”
mentioning
confidence: 99%
“…The rapid development of computational techniques based on the finite element method (FEM) allows vibration analysis of the systems of complex geometry and design to be conducted [1]. In [2], the finite element (FE) models are used to analyze the static and dynamic behavior of the EDM (electrical discharge machining) machine. The authors [3] analyzed cyclically loaded gear vibrations with a power circulation test rig configuration using FEM techniques.…”
mentioning
confidence: 99%
“…In this study, the drafting devices were simplified without affecting the solutions, which helped to save computing time and achieve convergence. 23 In addition, due to the symmetry of the drafting devices, DAD and NDS finite element models with a 3 mm width were created for the simulation to conserve analysis resources and boost the analysis efficiency (shown in Figure 3). The perimeters of the top and bottom rubber aprons in DAD were 246 mm and 582 mm, respectively.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The test was used to study the influence of wind, sand and other factors on the corona of transmission line hardware by Zhao et al [6]. Using finite element software, Wang et al [7] analyzed the static and dynamic characteristics of the U-shaped ring by numerical simulation and found that the U-shaped ring had the most serious deformation at the sixth order. Lu [8] used ANSYS to analyze the statics and dynamics of the U-shaped ring, and obtained the maximum equivalent stress and dangerous contact area of the U-shaped ring.…”
Section: Introductionmentioning
confidence: 99%